Developing collaborative approaches to enhance the professional development of primary mathematics teachers. Issue 4 (3rd July 2016) - McNeill, Jane; Butt, Graham; Armstrong, Andy
Abstract : This research project promoted a collaborative model of professional development between lead teachers from three schools, supported by a project coordinator and a researcher from a local university. Each lead teacher worked with their head teacher to design, lead, and evaluate an innovative, personalised, and school-based mathematics continuing professional development (CPD) programme in their school. University staff helped to facilitate project meetings across the schools and monitored impacts within each school. Professional development meetings, involving all teachers and teaching assistants (TAs) from the schools ( n  = 55), were designed to encourage a whole-school approach. The project also provided structured opportunities for the lead teacher to work with colleagues in the classroom, for example, through lesson observation and/or collaborative teaching. The outcomes from this project confirmed that collaborative models of CPD, as opposed to transmission, formal training, and 'top-down' models, were welcomed by teachers and head teachers – some of whom reported early indications of improvements in student performance. Commenting on what constitutes the most effective forms of CPD, there was a reiteration of the importance of combining peer and external support through a collaborative process.